Three-Dimensional Magnetic Resonance Imaging of Glenohumeral Dysplasia in Neonatal Brachial Plexus Palsy. (20th January 2016) - Eismann, Emily A.; Laor, Tal; Cornwall, Roger
Abstract : Background: Existing quantitative measurements of glenohumeral dysplasia in children with unresolved neonatal brachial plexus palsy (NBPP) have been mostly limited to the axial plane. The purpose of this study was to describe the three-dimensional (3D) pathoanatomy of glenohumeral dysplasia using 3D magnetic resonance imaging (MRI) reformations. Methods: 3D MRI reformations of the scapula, glenoid labrum, and proximal part of the humerus were created from a volume-acquisition proton-density-weighted MRI sequence of both the affected and the unaffected shoulder of seventeen children less than six years of age with unresolved NBPP who had not undergone shoulder surgery. Glenoid retroversion and posterior humeral head displacement were measured on axial 2D images. Humeral head displacement in all planes, labral circumference, glenoid retroversion, glenoid declination, and scapular morphometric values were measured on 3D reformations. Contiguity of the humeral head with the labrum and the shape of the glenoid were classified. Measurements were compared between the affected and unaffected sides. Results: On 3D evaluation, the humeral head was completely posteriorly translated in ten patients but was never outside the glenoid labrum. Instead, in these patients, the humeral head was eccentrically articulating with the dysplastic glenoid and was contained by a posteriorly elongated labrum. Glenoid dysplasia was not limited to the axial plane. Less declination of the glenoid in the coronal plane correlated with greater 3D glenoid retroversion. Glenoid retroversion resulted from underdevelopment of the posterior aspect of the glenoid rather than overdevelopment of the anterior aspect of the glenoid. 3D measurements of greater glenoid retroversion and less declination correlated with 2D measurements of glenoid retroversion and posterior humeral head displacement. Conclusions: Posterior humeral head displacement in NBPP should not be considered a simple "dislocation." Glenohumeral dysplasia is not limited to the axial plane. Abnormal glenoid declination may have potential implications for the evaluation and treatment of shoulder weakness and contractures.